The Influence of Position and Number of Longitudinal Connection of Sengon Glulam Beams Towards Strength and Stiffness - Sutarno Sutarno; Prayitno Prayitno; Adreas Triwiyono (International Conference on Coastal and Delta Areas, 2017)
The demand of wood as construction material always increases. However, sawn-wood with large size is more difficult to find in the market due to decreasing in stock dimension. In addition, it makes price more expensive. Indonesia has many trees from fast-growing species: however, they have low wood quality, and still limited in usage. To obtain a better performance of fast-growing species as construction material, it needs to be combined to produce glulam. This research observed the influence of position and longitudinal connections of wood glulam beam on strength and stiffness with damage species of sengonglulam beams. Preliminary testing was done to obtain physical and mechanical properties of clear specimen of sengon wood, testing method followed ISO-1995 standard. Fifteen glulam beam specimens whichhad 70 mm wide, 200 mm depth, 3000 mm length were constructed: They represented variations of position and connection work of 0 %, 25 %, 50 %, 75 % and 100 %. Each layer of lumber glued with thermosetting phenol formaldehyde (PA-302) adhesive at pressure 1 up to 1,1MPa for 10 hour pressing time. The static lateral loading steps were done continuously until the beam was damaged. The result indicated that sengonwas V class of strength. Glulam testing showed that in terms of strength and stiffness, the higher the number of connections, the lower the value. The strength reduction percentages of 0%, 25%, 50%, 75% and 100% produced 0%, 13,08%. 28,11%. 29,42%. 70,72 %. Respectively and the degradation of glulam stiffness were 100%. 99,92%. 87,86%. 83,06%. 67,08%. The failure of glulam beam with 0% had a shear followed by flexure damages of 25%, 50%, 75% and 100%. A flexure damage was followed by shear damage. Keywords: Paraserianthesfalcataria, Connection, Glulam Beam, Strength, Stiffness.